Path Analysis on Factors Associated withthe Incidence of Diarrhea in Infants Aged 6-12 MonthsatKaranganyar Community Health Center,inPurbalingga, Indonesia - Narzah, Norma Arista; -, Pawito; Dharmawan, Ruben (Journal of Maternal and Child Health, 2016)
Background:ÃÂ A diarrheal disease is an endemic disease and has outbreak potential in Indonesia. In Indonesia (2012) the number of pain diarrhea on toddler reached 900 per 1,000 inhabitants. This study aimed to determine the factors associated to the incidence of diarrhea in infant aged 6-12 months.ÃÂ ÃÂ Subjects and Method: This was an observational analytic study withÃÂ crossÃÂ sectionalÃÂ design.ÃÂ This was conducted in Karanganyar Community Health Center, Purbalingga, Indonesia, in April-Mei 2016.ÃÂ A total of 100 subjects was selectedÃÂ FixedÃÂ Disease.ÃÂ The data was using theÃÂ questionnaire.ÃÂ The data analysis used path analysis.Results: There was a direct correlation between breast feeding, nutritional status, personal hygiene of mothers and infants, and the availability of basic sanitation with the incidence of diarrhea, and statisticallyÃÂ significant (b=ÃÂ 2.62; 95% CI=ÃÂ 1.00ÃÂ toÃÂ 4.24;ÃÂ p=ÃÂ 0.001), (b=ÃÂ 3.37;ÃÂ 95% CI =ÃÂ 0.61 to 6.12; p=0.017), (b=3.70; 95% CI=2.07 to 5.33; p<0.001), (b=3.00; 95% CI=0.69 to 5.32; p=0.011). There is a positive correlation between indirect breast feeding with the incidence of diarrhea through nutritional status, culture with the incidence of diarrhea through breast feeding, culture with the incidence of diarrhea through the facilitys individual mothers and babies, the availability of basic sanitation with diarrhea through individual facilitys mothers and babies, statistically significant (b=0.91;ÃÂ  95%CI =-0.28 to2.11;p=0.135), (b=1.83; 95% CI=0.95 to 2.22; p<0.001), (b=1.40;ÃÂ 95% CI=0.46 to 2.25; p=0.003), (b=1.10; 95% CI= -0.10 to 2.22; p=0.076).Conclusion: There is aÃÂ direct correlationÃÂ betweenÃÂ breast feeding,ÃÂ nutritional status,ÃÂ personal hygiene of mothers andÃÂ infants, andÃÂ the availability ofÃÂ basic sanitationÃÂ withÃÂ the incidence of diarrhea.ÃÂ There is indirect correlation betweenÃÂ breast milk withÃÂ the incidence of diarÃÂrhea through nutritional status, culture, personal of mother and infants, the availability of basic saniÃÂtationÃÂ withÃÂ diarrheaÃÂ throughÃÂ individual facilitysÃÂ mother andÃÂ the baby.Keywords:ÃÂ nutritional status, culture,ÃÂ human breast milk, sanitation,ÃÂ individualÃÂ hygiene, diarrheaCorrespondence:ÃÂ NormaÃÂ AristaÃÂ Narzah.Community Health Center, Karanganyar,ÃÂ Purbalingga,ÃÂ ÃÂ Indonesia. Email: normaaristanarzah@yahoo.com.ÃÂ Journal of Maternal and Child Health (2016), 1(1): 13-18https://doi.org/10.26911/thejmch.2016.01.01.03ÃÂ